Implementasi Program edukasi lingkungan melalui pengadaan bak sampah pada siswa MI Nurul Ittihad NW labuhan haji - Meidy sulfani Hikmah (Jurnal Medika: Medika, 2026)
Environmental cleanliness is a key factor in maintaining health and comfort, especially inschools, which are an important medium for fostering a sense of care forwaste. MI Nurul Ittihad NW labuhan haji faces the problem of a lack of awareness among students in the waste management, which causes accumulation andenvironmental pollution. This PKM program aims to design and create waste bins from bamboo and scrap wood as a means to increasestudents’ awareness and discipline in disposing of waste in its proper place. With aparticipatory approach that actively involves students, this program was implemented ove a period of 3 months, covering surveys, manufacturing, and education. The results show a significant increase in students’ awareness of cleanlinessand a reduction in waste in the scholl environment. This program is effectiveas an educational tool and a practical solution for improving the cleanliness of the school environmentan and building awareness among students from an early age